(untitled) (Materiali di Estetica. Terza serie, 2023)
The aim of this paper is to show the relationship between “health” and the “efficacy of colours” on human life. What is the importance of colours in our life? An interesting case, from a biological and philosophical point of view, is the neurologist and psychologist Goldstein’s investigation on colours. The first part of this article deals with his holistic theory of the human organism. The second part has to do with Goldstein and Rosenthal’s study on the effect of colours on the human organism (1930). The final part of this paper analyses the positive or negative impact of certain colours on our psycho-physical health.